Optimization of Enzymatic Synthesis of Betulinic Acid Amide in Organic Solvent by Response Surface Methodology (RSM) - Nurul Atikah Amin Yusof; Nursyamsyila Mat Hadzir; Siti Efliza Ashari; Nor Suhaila Mohamad Hanapi; Rossuriati Dol Hamid (Indonesian Journal of Chemistry, 2019)
Optimization of the lipase catalyzed enzymatic synthesis of betulinic acid amide in the presence of immobilized lipase, Novozym 435 from Candida antartica as a biocatalyst was studied. Response surface methodology (RSM) and 5-level-4-factor central-composite rotatable design (CCRD) were employed to evaluate the effects of the synthesis parameters, such as reaction time (20–36 h), reaction temperature (37–45 °C), substrate molar ratio of betulinic acid to butylamine (1:1–1:3), and enzyme amounts (80–120 mg) on the percentage yield of betulinic acid amide by direct amidation reaction. The optimum conditions for synthesis were: reaction time of 28 h 33 min, reaction temperature of 42.92 °C, substrate molar ratio of 1:2.21, and enzyme amount of 97.77 mg. The percentage yield of actual experimental values obtained 65.09% which compared well with the maximum predicted value of 67.23%. The obtained amide was characterized by GC, GCMS and 13C NMR. Betulinic acid amide (BAA) showed a better cytotoxicity compared to betulinic acid as the concentration inhibited 50% of the cell growth (IC50) against MDA-MB-231 cell line (IC50 < 30 µg/mL).